2016
DOI: 10.1007/s40263-016-0335-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Psychotropic Medications in the Management of Anorexia Nervosa: Rationale, Evidence and Future Prospects

Abstract: Anorexia nervosa is a severe psychiatric disorder without approved medication intervention. Every class of psychoactive medication has been tried to improve treatment outcome; however, randomized controlled trials have been ambiguous at best and across studies have not shown robust improvements in weight gain and recovery. Here we review the available literature on pharmacological interventions since anorexia nervosa came to greater public recognition in the 1960s. This will include a critical review of why th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 185 publications
0
73
0
3
Order By: Relevance
“…The subcutaneous mode of application may also have promoted expectation effects. However, for the following reasons we consider it highly unlikely that such effects in total explain our results: (i) In general, AN is one of the most difficult disorders in psychiatry to treat 2,59 ; particularly achievement of weight gain is notoriously challenging in this disorder 4,60 . In clinical terms, we are unaware of any evidence for the occurrence of pronounced expectation effects in acutely ill patients.…”
Section: Discussionmentioning
confidence: 98%
“…The subcutaneous mode of application may also have promoted expectation effects. However, for the following reasons we consider it highly unlikely that such effects in total explain our results: (i) In general, AN is one of the most difficult disorders in psychiatry to treat 2,59 ; particularly achievement of weight gain is notoriously challenging in this disorder 4,60 . In clinical terms, we are unaware of any evidence for the occurrence of pronounced expectation effects in acutely ill patients.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the lack of efficacious pharmacological interventions specifically for AN might be due to a relative lack of insight about the biological mechanisms underlying it. [7][8][9] The fact that there is no clearly superior psychosocial intervention among a wide range of interventions for adults and adolescents with AN is also particularly concerning. 10 Despite the poor mechanistic knowledge of ED, an extensive body of literature has investigated putative risk factors for ED, testing a wide range of environmental [11][12][13][14][15] and genetic [16][17][18][19][20] risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Anorexia nervosa is a severe psychiatric disorder associated with food avoidance and life threatening weight loss that most commonly occurs in females (American Psychiatric Association, 2013). No medication has been approved for the treatment of anorexia nervosa (Frank & Shott, 2016). Basic science has suggested that dopamine receptor agonists support learning and behavior change in females who are underweight and in a low estrogen state (Frank, 2014).…”
Section: A R I P Ip R a Z O L E I N A N O R E X Ia N E R V O S Amentioning
confidence: 99%
“…No medication has been approved for the treatment of anorexia nervosa (Frank & Shott, 2016). Basic science has suggested that dopamine receptor agonists support learning and behavior change in females who are underweight and in a low estrogen state (Frank, 2014).…”
mentioning
confidence: 99%